Transplanting increases the leaf production rate in rice, consequently modifying plant development and growth - Clerget, Benoit; Pasuquin, Estela; Carandang, Rene; Domingo, Abigail J.; Layaoen, Heathel L.; Bueno, Crisanta (Cold Spring Harbor Laboratory, 2021)
In Asia, direct sowing and water savings are major trends in previously transplanted and flooded irrigated rice systems because of the higher cost of wages and increasing water shortage. Previous experiments showed that the leaf appearance rate varies between aerobic and flooded cropping systems. This study aimed to further understand how the planting method affects the development rate, flowering time, and yield of lowland irrigated rice crops. A two-year experiment was undertaken at the International Rice Research Institute, Philippines, using three contrasting rice varieties and three planting methods (transplanted, wet direct-seeded, and dry direct-seeded; at a density of 25 plants m-2) in a field submerged in 3–5 cm water from two weeks after the transplanting date. The effect of the planting method was similar in the three varieties, mostly without interaction between the two factors. In 2013, the leaf number of seedlings grown in seedling trays was two leaves behind that of direct-seeded plants at the time of transplanting. However, the young transplanted plants recovered quickly; produced new leaves at a faster rate (with a shorter phyllochron); reached panicle initiation, flag-leaf emergence and flowering time 1 week later; and developed more leaves compared to the direct-seeded plants. In 2014, growing in the nursery induced no delay in leaf appearance due to temperatures lower than those in 2013; therefore, the planting method did not affect the leaf appearance rate. Thus, plant development was primarily delayed by the density stress in the seedling trays under warm temperatures; however, the transplanted rice plants had lower plastochron duration than the direct-seeded plants, which made up for the initial delay in leaf appearance. In both years and at similar plant density, the transplanted plants produced more tillers bearing larger upper leaves that led to a higher leaf area index; however, grain yields were similar for the transplanted and direct-seeded crops.Highlights - In seedling trays, leaf appearance stopped at the appearance of the fourth leaf. - After transplanting, leaf appearance resumed at a faster rate than in direct-seeded plants. - Transplanted plants had delayed panicle initiation and flowering time, more tillers, and more and larger leaves per tiller, but similar grain yield compared to direct-seeded plants at similar planting density.